Nigerian Pidgin in the 21st Century: Any Hope of surviving the Opposition from English, Nigerian Languages and Foreign Languages? - Iwuchukwu, Godwin C.S.; Okafor, Monica (Advances in Social Sciences Research Journal, 2017)
Nigeria’s multilingual background provides a veritable ground for the emergence of pidgin–(abridge language for inter-ethnic communication and interaction), as a formidable National language. However, several growing opposing forces tend to make the realization of such dream in the 21st century a fantasy rather than reality. This paper set out to x-ray the developmental strides of the Nigerian pidgin in the late 20thCenturyto the first decade of the 21st century, research interest in some aspects of Nigerian pidgin, efforts by organizations for the promotion of Nigerian pidgin as well as factors that tendto work against further growth of the Nigerian pidgin. Our findings are that government policy thrust, growing mother tongue consciousness occasioned by the need to avoid language death or extinction, language endangerment, promotion of English language and other foreignlanguages such as French and Arabic as well as other sociolinguistic realities in the Nigerian speech communities may stifle if not stop completely the growth and influence of Nigerianpidgin in the 21st century.